2020
DOI: 10.3390/ijms21124215
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 Alleviates Aβ(25-35)-Induced Tau Hyperphosphorylation, Excessive Reactive Oxygen Species, and Apoptosis Through Interplay with Glial Cell Line-Derived Neurotrophic Factor Signaling in SH-SY5Y Cells

Abstract: Amyloid beta (Aβ) accumulation in the brain is one of the major pathological features of Alzheimer’s disease. The active form of vitamin D (1,25(OH)2D3), which acts via its nuclear hormone receptor, vitamin D receptor (VDR), has been implicated in the treatment of Aβ pathology, and is thus considered as a neuroprotective agent. However, its underlying molecular mechanisms of action are not yet fully understood. Here, we aim to investigate whether the molecular mechanisms of 1,25(OH)2D3 in ameliorating Aβ toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Our results support the relieving effect of calcitriol on parthanatos. Calcitriol increases the expression of GDNF and nuclear factor erythroid-2-related factor 2 to protect cells from damage caused by ROS, which is in accordance with our results (Pertile et al, 2018;Lin et al, 2020). Next, we verified the role of calcitriol in the MPTP mouse model.…”
Section: Discussionsupporting
confidence: 89%
“…Our results support the relieving effect of calcitriol on parthanatos. Calcitriol increases the expression of GDNF and nuclear factor erythroid-2-related factor 2 to protect cells from damage caused by ROS, which is in accordance with our results (Pertile et al, 2018;Lin et al, 2020). Next, we verified the role of calcitriol in the MPTP mouse model.…”
Section: Discussionsupporting
confidence: 89%
“…Vitamin D supplementation in this model improves memory possibly via the suppression of collapsin response mediator protein-2 (CRMP2) phosphorylation [ 158 ]. An in vitro study has also shown 1,25(OH) 2 D 3 alleviates Tau hyperphosphorylation and reduces ROS in a neuronal cell model treated with Aβ possibly via vitamin D’s role in enhancing GDNF [ 159 ].…”
Section: Vitamin D Is Neuroprotective In Neurons and Adult Brainmentioning
confidence: 99%
“…It also regulates gene expression of the low-affinity NGF receptor, p75NRT [ 85 ]. Moreover, 1,25(OH)2D3 was shown to be neuroprotective in an in vitro model of Alzheimer’s Disease through the restoration of Aβ-induced decrease in GDNF level and activation of the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt)/glycogen synthase kinase-3β (GSK-3β) pathway [ 86 ]. Both epidemiological data and results from animal experiments suggest that vitamin D3 deficiency may be a significant factor in increasing the risk of multiple sclerosis, diabetes, schizophrenia, and certain cancers, as well as SARS-CoV-2 virus infections [ 87 , 88 ].…”
Section: The Effects Of Vitamin D3 In the Cnsmentioning
confidence: 99%